2012
DOI: 10.3390/polym4021065
|View full text |Cite
|
Sign up to set email alerts
|

Calcite Biohybrids as Microenvironment for Stem Cells

Abstract: Abstract:A new type of composite 3D biomaterial that provides extracellular cues that govern the differentiation processes of mesenchymal stem cells (MSCs) has been developed. In the present study, we evaluated the chondrogenecity of a biohybrid composed of a calcium carbonate scaffold in its calcite polymorph and hyaluronic acid (HA). The source of the calcite scaffolding is an exoskeleton of a sea barnacle Tetraclita rifotincta (T. rifotincta), Pilsbry (1916). The combination of a calcium carbonate-based bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Thus, our study resulted in the development of a new biomimetic product, utilizing mollusk hemocytes, which is based on ex vivo synthetized ACC and calcite tightly bound to the surface of sponge chitin used as 3D scaffold. The outlook of this biomimetic direction includes numerous open questions concerning the role of hemocytes in the creation of a fine-tuned microenvironment [158] which is necessary for calcification ex vivo. Without doubt, the mechanisms and kinetics of this kind of biomineralization should be investigated, in addition to carrying out further studies on mechanical properties of developed mineralized scaffolds aimed at practical application in biomedicine, in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our study resulted in the development of a new biomimetic product, utilizing mollusk hemocytes, which is based on ex vivo synthetized ACC and calcite tightly bound to the surface of sponge chitin used as 3D scaffold. The outlook of this biomimetic direction includes numerous open questions concerning the role of hemocytes in the creation of a fine-tuned microenvironment [158] which is necessary for calcification ex vivo. Without doubt, the mechanisms and kinetics of this kind of biomineralization should be investigated, in addition to carrying out further studies on mechanical properties of developed mineralized scaffolds aimed at practical application in biomedicine, in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…The staining of collagen type 1 also acted as a marker for cell differentiation into osteoblasts. The increasing concentrations of collagen type 1 with time (stained green) suggest that cells are differentiating into osteoblasts in all tested samples [26].…”
Section: Osteogenic Differentiation and Cell Mineralisationmentioning
confidence: 94%
“…The production of collagen type I and type II by stem cells prior to differentiation is known [19,47,50]. However, depending on the cell line, collagen type I gene is upregulated and collagen type II is downregulated during osteogenesis, after 7 and/or 14 days [26,45,47,50].…”
Section: Cell Differentiation and Biomineralisationmentioning
confidence: 99%
“…The evidence of ALP activity on such materials suggested that they are worthy of further investigation into their potential for bone tissue engineering, particularly in light of studies of MC3T3 cells grown on CaCO 3 scaffolds which exhibited markedly increased ALP activity, higher levels of growth factors which regulate osteoblast differentiation, and matrix mineralization (calcium deposition), all of which are important biomarkers for bone tissue formation . Such results demonstrate the potential benefit of employing CaCO 3 scaffolds for bone tissue engineering applications …”
mentioning
confidence: 89%
“…With a view to demonstrating potential applications of this photochemistry approach, we mineralized the polymer‐modified silks. The carboxylic acid residues displayed on the proteins (C‐terminus, aspartic acid, glutamic acid) and polymers (PAA and PMAA) can bind Ca 2+ ions enabling the deposition of CaCO 3 , which is of interest for biomedical applications, for example, in bone tissue regeneration . SEM ( Figure 3 ) revealed the deposition of CaCO 3 crystals on the surface of silk fibers and films.…”
mentioning
confidence: 99%